2016
DOI: 10.1177/1475472x16666633
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding noise from a beveled trailing edge

Abstract: Coherent vortex shedding from blunt and beveled trailing edges generates tonal noise, which is usually undesired. To obtain a better understanding of the noise generation under such conditions, the flow field around a beveled trailing edge was characterized for Reynolds numbers based on the bluntness ranging from 2.5 × 104 to 5.1 × 104. Flow field statistics were obtained by means of planar high-speed two-component and stereoscopic particle image velocimetry measurements. The development of the shear layers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…An array consisting of 64 microphones with an effective diameter of 0.9 m was used. The array configuration followed a planar multi-arm logarithmic spiral distribution ( [19,20]), as illustrated in figure 2. The array plane was parallel to the center plane of the wind tunnel and located at a distance of 1.05 m as illustrated in figure 3.…”
Section: Acoustic Measurementsmentioning
confidence: 99%
“…An array consisting of 64 microphones with an effective diameter of 0.9 m was used. The array configuration followed a planar multi-arm logarithmic spiral distribution ( [19,20]), as illustrated in figure 2. The array plane was parallel to the center plane of the wind tunnel and located at a distance of 1.05 m as illustrated in figure 3.…”
Section: Acoustic Measurementsmentioning
confidence: 99%
“…An array with 64 microphones and of an effective diameter, D, of 0.9 m was used, arranged in a multi-arm logarithmic spiral configuration (Mueller 2002;Pröbsting et al 2016), as shown in Fig. 6.…”
Section: Microphone Arraymentioning
confidence: 99%
“…The distribution of the 64-microphone array is also shown. It follows a multi-arm logarithmic spiral configuration [23,26] with a diameter of 0.9 m.…”
Section: Methodsmentioning
confidence: 99%